OPINI AUDIT GOING CONCERN: FAKTOR-FAKTOR YANG MEMENGARUHI - Dewi Retnosari; Prima Apriwenni (Jurnal Akuntansi, 2021)
Going Concerned is one of the considerations seen by investors before making an investment. Going concern audit opinion is an audit opinion issued by the auditor to determine whether the entity can maintain its life within a certain period of time. The object of research used in this study is the infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2018 - 2020. The sample of this study consisted of 44 companies so that the observation data obtained 132 data. The sampling technique used the purposive sampling method. The data analysis method used is the descriptive statistical test, classical assumption test of normality, multicollinearity, autocorrelation, regression model feasibility test, overall model fit test, coefficient of determination test, logistic regression model test, partial model significance test, and simultaneous test with SPSS application. version 25. The conclusion of this study shows that the profitability ratio has a negative effect on going-concern audit opinion. While the ratio of liquidity and solvency has no effect ongoing concern audit opinion. Keywords: Profitability, Liquidity, Solvency, Audit Opinion, Going Concern. References: Ghozali, I. (2018). Aplikasi Analisis Multivariate Dengan Program IBM SPSS 25. Edisi 9.Semarang: Badan Penerbit Universitas Diponnegoro. Hery. (2015). Analisis Laporan Keuangan: Pendekatan Rasio Keuangan. Yogyakarta : CAPS (Center for Academic Publishing Service). Ikatan Akuntan Indonesia. (2011). PSA 29 Seksi 508: Laporan Auditor Independen Atas Laporan Keuangan. 29, 1–23. Indriyani (Akademi Maritim Nusantara), & Pandasari, T. (Universitas M. P. (2019). Pengaruh Current Ratio Dan Return On Asset (ROA) Terhadap Opini Audit Going Concern Perusahaan Pelayaran Yang Go Publik Periode 2012-2016. Jurnal Manajemen Dan Bisnis media ekonomi, XIX(1), 182–189. Institut Akuntan Publik Indonesia. (2011). PSA No. 30 SA Seksi 341. Standar Profesional Akuntan Publik, 30, 2. Investasi.kontan (2018), Ini yang jadi penyebab Turba alam manunggal (TRUB) didelisting, https://investasi.kontan.co.id/news/ini-yang-jadi-penyebab truba-alam-manunggal-trub-didelisting Irwanto, F., & Tanusdjaja, H. (2020). Pengaruh Profitabilitas, Likuiditas, dan Solvabilitas terhadap Opini Audit Terkait Going Concern (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2015-2017). Jurnal Multiparadigma Akuntansi Tarumanagara, 2(1), 298–307. Jensen, Michael C. dan W.H. Meckling. (1976). Theory of The Firm: Managerial Behavior, Agency Cost and Ownership Structure, Journal of Financial Economics 3. Hal 305-360. Kasmir. (2017). Analisis Laporan Keuangan. Jakarta: PT Rajagrafindo Persada. Miraningtyas, A. S. A., & Yudowati, S. P. (2019). Pengaruh Likuiditas, Reputasi Auditor dan Disclossure terhadap pemberian Opini Audit Going Concern (Studi Pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017) Anindya. Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 3(3), 76–85. Mutsanna, H., & Sukirno, S. (2020). Faktor Determinan Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018. Nominal: Barometer Riset Akuntansi Dan Manajemen, 9(2), 112–131. Petronela, T. A. (2004). Pertimbangan going concern perusahaan dalam pemberian opini audit. Fakultas Ekonomi Universitas Katolik Indonesia Atma Jaya, 1(1996), 46–55. Rahmadona, S., Sukartini, & Djefris, D. (2019). Faktor-Faktor Yang Mempengaruhi Opini Audit Going Concern (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017). Akuntansi Dan Manajemen, 14(1), 15–42. Rahman, M. A., & Ahmad, H. (2018). Pengaruh Likuiditas, Profitabilitas, dan Solvabilitas Terhadap Opini Audit Going Concern. Jurnal Akuntansi, 1(2), 44–55. Riyadi, T. (2019). Analisis Pengaruh Rasio Profitabilitas, Likuiditas, Solvabilitas dan Arus Kas Terhadap Opini Audit (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia). Jurnal Renaissance, 4(1), 465–478. Sahamok,net (2018), Saham delisting 2018 di BEI, akses 21 Januari 2020, Sartono, Agus. 2010. Menejemen Keuangan Teori dan Aplikasi. Edisi 4. BPFE Yogyakarta Spence, M., 1973. Job market signaling. Quarterly Journal of Economics, 87: 355-374 Wijaya, S., Dewi, K., Monica, M., Tendatio, C., Sitepu, W. R. B., & Dinarianti, R. (2019). Pengaruh Audit Committee, Audit Quality, Solvability, dan Sales Growth terhadap Going Concern Audit Opinion pada Perusahaan Industri Dasar dan Kimia yang terdaftar di Bursa Efek Indonesia periode 2014-2017. Jesya (Jurnal Ekonomi & Ekonomi Syariah), 2(2), 17–38.